The role and functions of public councils in enhancing effectiveness of regional state authorities - Orlova, I.V.; Sokolova, T.D. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2017)
The authors examine functions and activities of public councils as subjects of public control, and provide data on the legal regulation of public control and activities of its subjects in the Russian Federation. The article underlines the following main problems in the work of public councils: the fragmented legal regulation, and the low public involvement in solving socially significant problems that require active participation of citizens. The article is based on the empirical study conducted in 2015-2016 by the Committee of Public Relations of the Government of Moscow in cooperation with the Public Chamber of Moscow according to the orders of the Russian President given at the plenary session of the Public Chamber on 23.06.2015 in the framework of monitoring the effectiveness of public councils under the executive branch of the Federation subjects. The study of the activities of public councils under the state and local authorities was conducted in the form of a survey, which revealed that the public councils under the executive bodies of Moscow do not pursue a coordinated policy in respect of personnel, functions and regulations, and often perform different and incomparable in scale functions. Based on the research findings, the authors suggest some measures to enhance the effectiveness of public councils, such as unification of legal regulations and working formats, which would improve public awareness of the public councils’ activities and of the opportunities of personal involvement in such. However, the raising awareness and increasing interest in the public control should be accompanied by the development of effective mechanisms of involvement in the public control practices.